Students' attitudes on electronic English learning - Nur, Dedi Rahman; Maharani, Yosieka Maharani; Sukaena, Sukaena (Journal of English Language and Pedagogy, 2021)
Abstract: Along with the development of technology in various aspects of life, it makes technology have a big impact and influence in today's life. In educational sector, one of the roles of technology in learning activities is to support the learning activities become easier to accomplished and interesting. One of the developments of technology in education sector is e-learning. E-learning may be an option to be used on class as a learning tool. Especially, on English subject when some students may find it difficult then e-learning could be their alternative to learn English the significance of this study for find out the students’ perspective regarding e-learning in English subject. The data was conducted by distributing questionnaire to students. The study conducted in Bunga Bangsa Islamic Junior High School involving 56 students. Questionnaire was used as an instrument to collect the data which score analyzed based on the mean score. The result showed that students have positive attitudes toward e-learning. In terms of students’ attitudes, it is found that students have positive attitudes toward e-learning since they found e-learning is appropriate to use, effective, and excellent technique to help them learning English.  Keywords: attitudes, belief, e-learning.